Sistem Informasi Transaksi Alat-Alat Kesehatan Berbasis Web Pada PT. Cipta Multi Persada - Putri Ariyani, Safira; Kurniawan, Yudi (CV. Shofanah Media Berkah, 2023)
The need for health services for the community is increasing. However, the health facilities provided, especially in the field of providing medical equipment, have not been managed properly. Therefore, an adequate service is needed, in this case especially the transaction service for medical devices. In order to realize a good service, we need an information processing system that can be used to manage transactions from these medical device products. PT. Cipta Multi Persada, located in South Tangerang, is a business unit engaged in the provision of medical equipment. Currently, transaction activities are still carried out manually, apart from that, the marketing reach of medical device products is still on a local scale so that the income obtained is still not optimal. This study aims to build a transaction information system for medical devices at PT. Cipta Multi Persada. Writing this thesis takes the object of the transaction system at PT. Cipta Multi Persada. The system development method used is the SDLC (System Development Life Cycle) method. The results of this study are e-commerce-based online sales systems can be done easily to market and sell products with transactions through the website so that they can reach consumers in a clearer scope.